The Relative Age Effect in Handball: Its Existence and Influence on Playing Position for Youth and Junior Asian National Teams - Alsharji, Khaled E.; Alkatan, Mohammed F.; Akbar, Abdullah A.; Ahmad, Hasan A. (Dirasat: Educational Sciences, 2020)
There was significant RAE for the Asian national handball players (X2 (3) = 44.511, p <.001), youth teams (X2 (3) 30.189, p= <.001), and junior level (X2 (3) = 15.000, p=.002) with a greater proportion of players born in Q1. For Asian national players, goalkeepers (X2 (3) = 8.937, p =.03), backs (X2 (3) = 26.797, p <.001), and wings (X2 (3) = 10.628, p =.014), were significantly affected by RAE. For youth teams, backs (X2 (3) = 17.520, p =.001) and wings (X2 (3) = 14.556, p =.002) were significantly affected by RAE. For junior goalkeepers (X2 (3) = 10.040, p =.018) and backs (X2 (3) = 10.625, p =.014) were significantly affected by RAE. The results of the current study agree with other than handball literature confirming the benefits athletes experience for being born in the first quarter of the year and demonstrates that RAE has a significant impact in Asian national youth and junior handball teams.